Financial Distress and Earnings Management An Empirical Study of Non-Financial Firms Listed on the Indonesia Stock Exchange - Ayu Sheila Soraya; Dianwicaksih Arieftiara (Publikasi Indonesia, 2024)
This study examines the relationship between financial distress and earnings management among non-financial firms listed on the Indonesia Stock Exchange during the period 2018–2022. The research employs a quantitative approach using the modified Jones model to measure discretionary accruals, with leverage, firm size, and profitability included as control variables. The findings reveal that profitability has the strongest positive influence on earnings management, indicating that firms with higher profitability are more likely to manipulate earnings to enhance financial results and meet market expectations. Conversely, leverage demonstrates a significant negative effect, suggesting that firms with higher debt levels are less likely to engage in earnings manipulation due to increased creditor scrutiny and financial discipline. Meanwhile, financial distress and firm size have minimal impacts, with their coefficients showing no significant influence on discretionary accruals. These results highlight the importance of profitability and leverage as key drivers of earnings management while suggesting that financial distress and firm size play lesser roles in this context. The study acknowledges limitations, including its focus on non-financial firms in Indonesia, a five-year observation period, and the exclusion of additional factors like governance and macroeconomic conditions. Future research could address these limitations by expanding the dataset, incorporating more variables, and exploring other emerging markets.